1983
DOI: 10.3406/arss.1983.2178
|View full text |Cite
|
Sign up to set email alerts
|

Langage et pratiques sociales

Abstract: Sprache und soziale Praktiken. Gegenstand der gleichermaßen linguistischen wie soziologischen Analyse ist eine aus einem Pariser Vorort stammende Gruppe von Jugendlichen proletarischer Herkunft. Von den in der soziologischen Taxinomie gemeinhin verwendeten Kriterien her gesehen (Alter, Geschlecht, soziale Herkunft, Wohnort, usw.), weist diese peer group tatsachlich homogenen Charakter auf. Die soziolinguistische Analyse zweier Reihen von Variablen — die Vokalöffnung und der Wegfall des /l/ bei den Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 1 publication
0
11
0
6
Order By: Relevance
“…Paris, like any other large metropolitan area, is characterized by significant linguistic variation. Studies have shown that Parisian French has a complex hierarchy dependent on social situations and classes (Laks 1977), and that variation within social classes takes place in ways than cannot be accounted for only by socio‐economic status (Laks 1983). Even within the social class reputed to represent normative French, there is a great deal of variation in performance (Martinet and Walter 1973) and in attitudes (Gueunier, Genouvrier and Khomsi 1978).…”
Section: Description Of the Present Studymentioning
confidence: 99%
“…Paris, like any other large metropolitan area, is characterized by significant linguistic variation. Studies have shown that Parisian French has a complex hierarchy dependent on social situations and classes (Laks 1977), and that variation within social classes takes place in ways than cannot be accounted for only by socio‐economic status (Laks 1983). Even within the social class reputed to represent normative French, there is a great deal of variation in performance (Martinet and Walter 1973) and in attitudes (Gueunier, Genouvrier and Khomsi 1978).…”
Section: Description Of the Present Studymentioning
confidence: 99%
“…On la retrouve, entre autres, en français de France où elle se présente avec une plus ou moins grande vivacité en fonction, notamment, d'une variation de type diastratique (Laks, 1983). Cette utilisation particulière, qui traduit sanséquivoque l'intégration d'un marqueur dans le système des connecteurs neutres, n'est pas propre au français québécois (v. par exemple le Glossaire du Parler français au Canada aux entrées pis adverbe, pis conjonction, pis après locution adverbiale et pis ensuite locution adverbiale).…”
Section: Le Connecteurunclassified
“…pour devenir des connecteurs neutres (Antoine, 1958;Laks, 1983). pour devenir des connecteurs neutres (Antoine, 1958;Laks, 1983).…”
Section: Introductionunclassified
“…On pourrait citer d'autres travaux conduisant à des résultats semblables et, notamment, ceux de sociologues qui ont étudié la question de l'insertion des jeunes sortis de l'école en échec (Dubar (Éd. ), 1987, Nizet & Hiernaux 1984Laks, 1983). Ces différentes études mettent en évidence que ces adolescents ont fréquemment construit des images de soi d'hommes sans qualité Ces travaux valident, dans ses grandes lignes, l'hypothèse de Linda Gottfredson (1981) selon laquelle, à l'école, un adolescent apprend à déterminer la limite supérieure des positions sociales qu'il peut espérer atteindre.…”
Section: L'école : Un Miroir Structuré Structurant L'image Scolaire Dunclassified